ICTs are shaping the future of ACP agriculture - Greenidge, Carl B. (Technical Centre for Agricultural and Rural Cooperation, 2004)
Carl B. Greenidge explains that policy makers should encourage the use of ICTs, and make the identification of promising applications part of their daily routines.